A mixed methods evaluation of the Youth Focused Social Network Initiative for safe abortion in Rupandehi, Nepal. - Khanal, Ram Chandra; Menzel, Jamie; Gurung, Swadesh; Jones, Lea; Andersen, Kathryn (International Journal of Child & Adolescent Health, 2017)
The Youth Focused Social Network Initiative (YFSNI) was a program to increase young women's knowledge of and skills in accessing comprehensive abortion care (CAC) in Rupandehi, Nepal from 2012-2014. The program trained peer educators to provide information and support related to CAC and encouraged adults to support youth in their communities. The objective of this study is to evaluate the effectiveness of the YFSNI through a mixed methods evaluation of change in young women's knowledge and attitudes about accessing CAC after the intervention. Methods: Cross-sectional baseline (n = 600) and endline (n = 480) quantitative surveys were conducted among women ages 18-24. Quantitative analyses included bivariate, logistic regression and difference-in-differences models, the latter two adjusted for key socio-demographic characteristics. Qualitative in-depth interviews were conducted with project staff, providers, peer leaders and their families. Qualitative interviews were analyzed for key themes around acceptability and support for youth reproductive health. Results: At endline, women in the intervention group who reported exposure to peer education had significantly higher odds of knowing the legality of abortion (3.4; 95% CI 1.9-6.0) and were more likely to feel comfortable initiating discussions about abortion-related issues with friends (7.5; CI 2.8-19.6) compared with those who were not exposed. Difference-in-difference models showed higher odds of feeling comfortable speaking with a provider about abortion-related issues for women in the intervention group (OR 2.5; 95% CI 1.0-6.0). Conclusions: The YFSNI evaluation shows positive results in youth CAC knowledge and attitudes. Program expansion should be considered in light of continued need in Nepal.